PERLINDUNGAN HUKUM TERHADAP HAK MASYARAKAT ADAT T`EBA TIMUR ATAS SENGKETA TANAH ULAYAT OLEH UNIT PELAKSANA TEKNIS DAERAH (UPTD) KESATUAN PENGELOLAAN HUTAN (KPH), DI DESA T`EBA TIMUR KECAMATAN BIBOKI TAN PAH KABUPATEN TIMOR TENGAH UTARA - Camelia Melkitidis Ukat; Juliana Susantje Ndolu; Petornius Damat; Husni Kususma Dinata (STKIP Subang, 2026)
Customary land is land controlled and managed collectively by indigenous communities based on customary law that has been inherited from generation to generation. For the indigenous community of Teba Timur, customary land holds significant social, cultural, economic, and spiritual value as a source of livelihood and communal identity. However, a dispute arose when the Regional Technical Implementation Unit of Forest Management (UPTD KPH) claimed the area as part of a state forest zone, resulting in restrictions on the community’s rights to manage and utilize their customary land. This study aims to examine: (1) the customary legal basis of the Teba Timur indigenous community over customary land that has been traditionally controlled and managed, and (2) the perspective of Indonesian positive law regarding the control and management of land by the UPTD KPH over the customary land of the Teba Timur indigenous community. This research employed an empirical juridical method with a qualitative approach. Data were collected through interviews with village officials, customary leaders, community members, and UPTD KPH personnel, as well as literature studies on relevant legal regulations. The findings indicate that the Teba Timur indigenous community possesses a strong customary legal basis over its customary land due to continuous hereditary control and management. Although customary rights are recognized under Indonesian law, their implementation remains ineffective because of overlapping authority claims. Therefore, stronger legal protection, formal recognition of indigenous communities, regulatory harmonization, and deliberative dispute resolution are required.